2020
DOI: 10.3390/ijerph17041457
|View full text |Cite
|
Sign up to set email alerts
|

Residential Radon and Histological Types of Lung Cancer: A Meta-Analysis of Case‒Control Studies

Abstract: Epidemiological studies on residential radon exposure and the risk of histological types of lung cancer have yielded inconsistent results. We conducted a meta-analysis on this topic and updated previous related meta-analyses. We searched the databases of Cochrane Library, Embase, PubMed, Web of Science and Chinese National Knowledge Infrastructure for papers published up to 13 November 2018. The pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using fixed and random effects models. Subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 60 publications
6
38
0
2
Order By: Relevance
“…Radon-attributable lung cancer deaths for all 66 countries totaled 226,057 in 2012 and represented a median of 3.0% of total cancer deaths [77]. Recently, multiple published studies have measured the risk of developing lung cancer following residential or occupational radon exposure in various regions of the world, as well as the synergistic effect of cigarette smoking and the effect in never-smokers [8][9][10]73,[77][78][79][80][81] as well as analyzing the histological types of lung cancer [82].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%
“…Radon-attributable lung cancer deaths for all 66 countries totaled 226,057 in 2012 and represented a median of 3.0% of total cancer deaths [77]. Recently, multiple published studies have measured the risk of developing lung cancer following residential or occupational radon exposure in various regions of the world, as well as the synergistic effect of cigarette smoking and the effect in never-smokers [8][9][10]73,[77][78][79][80][81] as well as analyzing the histological types of lung cancer [82].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%
“…Since 1990, numerous case-control studies have been conducted in both high-and low-radon areas in Europe, North America and China to assess the excess risks of lung cancer attributable to residential radon exposure . Due to the relatively small sample sizes of these case-control studies, large pooled collaborative studies [46][47][48][49][50][51][52] and several meta-analyses [53][54][55][56][57][58] were conducted, aiming to acquire similar statistical power as the epidemiologic studies of underground miners [59], as well as to provide a comparison of the pooled risk estimates with extrapolations from the miner-based risk models [49]. While the pooled collaborative studies have shown significant positive associations between residential radon exposure and lung cancer risk to varying degrees, all but one pooled study [52] assessed this association in populations of both ever-smokers and never-smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 39 reported on a meta-analysis of case–control studies on residential radon and lung cancer risk that showed for every 100 Bq m −3 , an increase in radon exposure was associated with a significant 7% increase in lung cancer risk. Li et al 40 reported radon exposure was associated with risk increases in lung cancer, small-cell lung carcinoma and adenocarcinoma by 11%, 19% and 13%, respectively. Therefore, the dose–response relationship is linear, i.e., the risk of lung cancer is proportional to radon exposure.…”
Section: Discussionmentioning
confidence: 99%